Prenylcysteine Oxidase 1 Is a Key Regulator of Adipogenesis - Cristina Banfi; Alice Mallia; Stefania Ghilardi; Maura Brioschi; Erica Gianazza; Sonia Eligini; Pelin Sahlén; Roberta Baetta (MDPI AG, 2023)
The process of adipogenesis involves the differentiation of preadipocytes into mature adipocytes. Excessive adipogenesis promotes obesity, a condition that increasingly threatens global health and contributes to the rapid rise of obesity-related diseases. We have recently shown that prenylcysteine oxidase 1 (PCYOX1) is a regulator of atherosclerosis-disease mechanisms, which acts through mechanisms not exclusively related to its pro-oxidant activity. To address the role of PCYOX1 in the adipogenic process, we extended our previous observations confirming that Pcyox1−/−/Apoe−/− mice fed a high-fat diet for 8 or 12 weeks showed significantly lower body weight, when compared to Pcyox1+/+/Apoe−/− mice, due to an evident reduction in visceral adipose content. We herein assessed the role of PCYOX1 in adipogenesis. Here, we found that PCYOX1 is expressed in adipose tissue, and, independently from its pro-oxidant enzymatic activity, is critical for adipogenesis. Pcyox1 gene silencing completely prevented the differentiation of 3T3-L1 preadipocytes, by acting as an upstream regulator of several key players, such as FABP4, PPARγ, C/EBPα. Proteomic analysis, performed by quantitative label-free mass spectrometry, further strengthened the role of PCYOX1 in adipogenesis by expanding the list of its downstream targets. Finally, the absence of Pcyox1 reduces the inflammatory markers in adipose tissue. These findings render PCYOX1 a novel adipogenic factor with possible pathophysiological or therapeutic potential.